Adjuvant use of antibiotics with corticosteroids in inflammatory bowel disease exacerbations requiring hospitalisation: a retrospective cohort study and meta‐analysis. Issue 1 (5th November 2015) - Gupta, V.; Rodrigues, R.; Nguyen, D.; Sauk, J.; Khalili, H.; Yajnik, V.; Ananthakrishnan, A. N.
Summary: Background: Patients hospitalised with an exacerbation of inflammatory bowel disease (IBD) often receive antibiotics in addition to intravenous steroids. However, their efficacy in this setting is unclear. Aim: To ascertain if the addition of antibiotics to intravenous steroids modifies short and long‐term clinical outcomes. Methods: Our study included IBD patients hospitalised between 2009 and 2014 who received intravenous (IV) steroids with or without adjuvant antibiotics. Outcomes of interest included length of stay (LOS), need for medical and surgical rescue therapy during the hospitalisation, and at 90 and 365 days. A meta‐analysis of previously published randomised trials was additionally performed. Results: A total of 354 patients were included [145 ulcerative colitis (UC); 209 Crohn's disease (CD)]. In CD, combination of IV steroids and antibiotics did not change need for in‐hospital medical rescue therapy, surgery or hospitalisations at 1 year but was associated with greater LOS (6.1 vs. 4.6 days, P = 0.02). In UC, patients receiving antibiotics were less likely to require in‐hospital medical rescue therapy [odds ratio (OR): 0.42, 95% confidence interval (CI): 0.19–0.93] but experienced no statistically significant differences in LOS, in‐hospital surgery, re‐hospitalisations or surgery by 1 year. A meta‐analysis of three relevant randomised trials demonstrated no difference in clinical improvement with antibiotics over placebo (OR: 1.08, 95% CI: 0.50–2.32). Conclusions: The addition of antibiotics to intravenous steroids for treatment of IBD exacerbations was associated with a reduced need for in‐hospital medical rescue therapy in ulcerative colitis without significant long‐term benefit, and did not affect short‐ or long‐term outcomes in Crohn's disease.